CULTURE, NATURE AND NURTURE: NIGHTCLUB WORKERS BEHAVIOUR IN BIRA, BULUKUMBA - Shermina Oruh (Jurnal Masyarakat dan Budaya, 2023)
Nightclub worker behavior has been considered as negative and immoral behavior by society because they have been practicing obnoxious attitude such as consuming alcohol, having intercourse, inhaling drugs, etc. Therefore, this study aimed to analyze the behavior of actors or nightclub workers at Bara nightclub in Bira Village, Bulukumba, South Sulawesi, Indonesia. This was a case study with participatory approach. In the results of this research, it was revealed that the behavior of nightclub workers came naturally and taught (nature and nurture). The behavior is of human is a result of human natural traits. Moreover, nurtured-behavior occurred because of the initiative of actors or nightclub workers when they saw a nightclub and found alcohol and they drank it until they lost control or consciousness. Nurture behavior is the behavior that is taught unconsciously when seeing and imitating the behavior of others or surrounding. Thus, human behavior is influenced by nature and nurture that resulted a new culture.